Effectiveness of morphemic analysis of Graeco-Latin word parts as a vocabulary learning strategy among ESL learners - Paiman, Norazha; Yap, Ngee Thai; Chan, Mei Yuit (Penerbit Universiti Kebangsaan Malaysia, 2015)
This study examined the effects of morphemic analysis of Graeco-Latin roots and affixes as a vocabulary learning strategy among Malaysian ESL learners. Three intact classes of undergraduates majoring in health sciences were assigned to three different treatments: Graeco-Latin morphemic analysis, general morphemic analysis and contextual clues. Participants in all groups undertook a five-week treatment intervention which was done biweekly and lasted for two hours. Before the five-week explicit instruction, participants sat for a pre-test where three vocabulary measures were elicited. During the treatment, ten reading texts were used by all students, but the strategies adopted in teaching the selected vocabulary items were different. The students in one group were taught Graeco-Latin morphemic analysis, while the second group was introduced to general morphemic analysis, and the final group focussed on the use of contextual clues. Each group was taught how to derive word meanings by using these three different strategies. After the five-week treatment, the students sat for a post-test which was identical to the pre-test taken earlier. The pre-test and post-test scores were analysed using the one-way ANOVA and paired sample T-test. The results indicated that (a) the group that were taught Graeco-Latin morphemic analysis scored the highest in all three vocabulary measures, (b) the group taught general morphemic analysis also improved slightly but (c) the group that was taught to use contextual clues showed no improvement in all three vocabulary measures. The findings suggest that morphemic analyses may be a better vocabulary learning strategy particularly for the health sciences.